2007
DOI: 10.1261/rna.359007
|View full text |Cite
|
Sign up to set email alerts
|

Induction of drug resistance and transformation in human cancer cells by the noncoding RNA CUDR

Abstract: Refractory to apoptosis induced by anticancer drugs is one of the major causes of drug resistance in human cancers. The involvement of noncoding RNA (ncRNA) in cancer cell drug resistance has not yet been reported. By using the technique of RT-PCR-based differential display, a novel gene, cancer up-regulated drug resistant (CUDR) gene, was found to be overexpressed in a doxorubicin-resistant subline of human squamous carcinoma A431 and A10A cells, which were also more resistant to druginduced apoptosis. The fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 20 publications
1
90
0
Order By: Relevance
“…We have also found that in other known proteins such as BCRP and MVP, which are known to render the cellular resistance to mitoxantrone, expressions could not be correlated for their role in mitoxantrone resistance in our studies. Recently, two noncoding RNAs (miR-221/222 and CUDR) have also been shown to play an important role in mediating drug resistance in cancer cells (25,26). In summary, this study has identified another noncoding RNA (vRNA-1) that plays an important role by mediating the drug-resistant phenotype of malignant cells.…”
Section: Discussionmentioning
confidence: 74%
“…We have also found that in other known proteins such as BCRP and MVP, which are known to render the cellular resistance to mitoxantrone, expressions could not be correlated for their role in mitoxantrone resistance in our studies. Recently, two noncoding RNAs (miR-221/222 and CUDR) have also been shown to play an important role in mediating drug resistance in cancer cells (25,26). In summary, this study has identified another noncoding RNA (vRNA-1) that plays an important role by mediating the drug-resistant phenotype of malignant cells.…”
Section: Discussionmentioning
confidence: 74%
“…92,93 Cancer upregulated drug resistant (CUDR) is an lncRNA that exhibits elevated expression in multiple cancers, including CRC. 94,95 Tsang et al 94 provided evidence that increasing CUDR gene levels in vitro in human squamous carcinoma cells resulted in increased resistance to doxorubicin and etoposide and decreased levels of drug-induced apoptosis via the downregulation of caspase-3. The question of whether similar mechanisms operate in CRC should be examined further, but this observation suggests that lncRNA manipulation-based gene therapy may be beneficial in overcoming drug resistance and in designing personalized therapeutics for cancer patients.…”
Section: Tumor Treatmentmentioning
confidence: 99%
“…In addition, there was evidence to suggest that CUDR was only expressed in human placenta but not in other normal tissues; CUDR was upregulated in human colon, cervix, and lung cancer (10). These results guided us to investigate the role of UCA1a(CUDR) in embryonic development and bladder cancer progression.…”
Section: The Expression Patterns Of Uca1a(cudr) In Cells and Tissuesmentioning
confidence: 99%
“…Interestingly, sequence comparison of the UCA1 and UCA1a(CUDR) cDNA revealed a 1,265 bp common region. CUDR was believed to exert its function as an lncRNA in the regulation of drug resistance and cellular transformation (10). In addition, CUDR was upregulated in various tumor tissues, including colon, cervix, and lung cancer (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation